Implementasi Nilai-Nilai Moderasi Beragama dalam Membentuk Karakter Siswa Moderat di Madrasah Tsanawiyah Miftahul Huda Kangayan Kabupaten Sumenep - Hasanah, Naslatul; Atho’, Saihul; Waslah, Waslah (Lembaga Yasin AlSys, 2025)
The increasing modernization of society demands that educational institutions shape students' character to prevent them from embracing values contrary to Islamic teachings. In this context, schools as formal educational institutions play a vital role as the second environment after the family in instilling noble values, including empathy and respect for diversity. This study aims to analyze the implementation of religious moderation values in shaping students into moderate, tolerant individuals who appreciate differences at MTs Miftahul Huda Kangayan, Sumenep Regency. A qualitative field study approach was employed, with data collected through observations and interviews involving MTs Miftahul Huda students, and analyzed using thematic analysis techniques. The findings show that the implementation of religious moderation values is carried out through direct instruction, interfaith discussions, and social activities, which significantly enhance students' awareness of the importance of tolerance and respect for diversity. Students demonstrated openness, dialogue-oriented attitudes, and constructive engagement in interfaith interactions. This implementation is further reinforced by the school's inclusive policy of employing non-Muslim teachers and admitting Christian students without discrimination, reflecting the institution’s moderate stance. The study concludes that the application of religious moderation values at MTs Miftahul Huda is not only effective in fostering moderate student character but also strengthens interreligious harmony within the school environment.